PELBARTUS OF THEMESWAR’S USE OF SOURCES IN THE “ROSARIUM”. A STATISTICAL STUDY - Alexandra BANEU (Studia Universitatis Babeș-Bolyai. Philosophia)
Pelbartus of Themeswar’s Use of Sources in the Rosarium. A Statistical Study. This article analyses Pelbartus of Themeswar’s use of sources in the first volume of the Rosarium. In order to make the mapping of influences easier we have divided the works cited into two categories: medieval and ancient writings. The group of medieval works is also divided into two subcategories: scotist commentaries on the Sentences of Peter Lombard and alphabetical Summae and Encyclopedias. These are the two types of works that have inspired the form of the Rosarium.